2002
DOI: 10.1038/sj.cdd.4400969
|View full text |Cite
|
Sign up to set email alerts
|

Recent insights into the mechanism of glucocorticosteroid-induced apoptosis

Abstract: Glucocorticosteroid hormones induce apoptosis in lymphocytes. Therefore, glucocorticoids are commonly used as immunosuppressive and chemotherapeutic agents. This review examines many facets of the process by which glucocorticoids induce apoptosis. This process is divided into three stages, an initiation stage that involves glucocorticoid receptor-mediated gene regulation, a decision stage that involves the counterbalancing influence of prosurvival and proapoptotic factors, and the execution stage which involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
178
0
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(192 citation statements)
references
References 113 publications
5
178
0
6
Order By: Relevance
“…8 Although there is some controversy about the role of this transcription factor in cell apoptosis, most data support an NF-kB antiapoptotic action. 28 In addition, it has been shown that cells that are naturally resistant to TNF-induced apoptosis become susceptible when transfected with an expression vector for IkBa, which inactivates NF-kB. 26 Consistent with these findings, we observed that the presence of FP and, to a greater extent, the combined presence of FP and salmeterol reduced the expression of phosphorylated IkBa, which, in turn, leads to an increased IkBa concentration and inhibition of NF-kB activity.…”
Section: Discussionsupporting
confidence: 80%
“…8 Although there is some controversy about the role of this transcription factor in cell apoptosis, most data support an NF-kB antiapoptotic action. 28 In addition, it has been shown that cells that are naturally resistant to TNF-induced apoptosis become susceptible when transfected with an expression vector for IkBa, which inactivates NF-kB. 26 Consistent with these findings, we observed that the presence of FP and, to a greater extent, the combined presence of FP and salmeterol reduced the expression of phosphorylated IkBa, which, in turn, leads to an increased IkBa concentration and inhibition of NF-kB activity.…”
Section: Discussionsupporting
confidence: 80%
“…This induction of apoptosis has also been proposed to be the main effector mechanism for the beneficial effects of GC treatment in lymphoid malignancies. 5 Evidence is accumulating that non-apoptotic programmed cell death (PCD), such as mitotic catastrophe, senescence, necrosis-like PCD and autophagy, may also play a role in the tumor response to anticancer drugs. 6,7 Autophagy is a well-conserved process, regulating normal cytoplasmic and organelle turnover, and is characterized by the formation of autophagosomes: double-or multiple-membrane-surrounded cytoplasmic vesicles engulfing cytoplasmic organelles such as mitochondria and endoplasmic reticulum.…”
mentioning
confidence: 99%
“…28,29 The anti-apoptotic Bcl-2 was able to protect against apoptosis, but not against the anti-proliferative responses induced by GC. 30 Furthermore, inhibition of the anti-apoptotic Bcl-xL sensitized T-ALL cells to Dex-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%